Bárbaros y griegos: políticas de lectura - García Quintela, Marco V. (Gerión. Revista de Historia Antigua, 1993)
The article deals with the two main religious festivals of the city of Stratonikeia (Caria, Asia Minor) devoted to the most important local deities: the Panamareia dedicated to Zeus Panamareus and the kleidos agoge, in honour of Hekate in Lagina. After considering the autochthon character of these deities and the causes of their religious popularity, the article makes an exposee of the religious activities enacted in those festivals according to the numerous Greek inscriptions of Stratonikeia (Panamara and Lagina included).